A feature–oriented approach to platform–specific modelling of coarse–grained components. (27th July 2012) - Feng, Jindan; Zhan, Dechen; Nie, Lanshun; Xu, Xiaofei
Coarse–grained–component–based software development improves efficiency when developing large–scale software for enterprises. However, there are no rigorous models to describe the component because of its structural complexity. Aiming to obtain a correct and formal model, this paper presents a feature–based platform–specific modelling approach for coarse–grained components. The component is described by the Feature Relationship Tree (FRT) from the perspectives of function and implementation. By establishing mapping between the feature model and the PSM, the meta–PSM of the component is defined on the basis of typical patterns. A practical case is described to validate the method in this paper.